The measurement and development of Georgian consumer prices - Cathleen Faber (Universität Potsdam, Wirtschafts- und Sozialwissenschaftliche Fakultät, 1999)
This paper presents in the first section a methodological introduction concerning statistics of consumer prices in Georgia. The second section gives a general idea of the development of consumer prices from January 1994 till September 1999. A detailed regional analysis is added in section 3. The fourth section analyses the development of consumer prices for the eight main groups included in the total CPI. Section 5 compares the changes in Georgian CPI with the movements of foreign exchange rates in Georgian Lari. This paper ends with a summary including a short outlook to the next years.
urn:nbn:de:kobv:517-opus-12139
Keywords: 330